The Influence of Work Family Conflict and Emotional Intelligence on Employee Performance Through Job Satisfaction as Intervening Variable - Rosyida, Abidatur; Sopiah, Sopiah; Churiyah, Madziatul (IJBLE Scientific Publications Community Inc., 2024)
This study aims to determine the effect of Work Family Conflict and Emotional Intelligence on Employee Performance with Job Satisfaction as an Intervening Variable. This research is important because of the research gap in previous studies. This study uses nonprobability sampling technique with purposive sampling method. The data collection technique used a questionnaire distributed to respondents with a 5-point Likert scale answer. Sample in this study amounted to 102 respondents with data analysis using the SEM-PLS method SmartPLS4 software. according to Table 4. The following findings: work family conflict has a positive and significant impact on job satisfaction; emotional intelligence has a positive and significant impact on job satisfaction; work family conflict has a negative and significant impact on employee performance; emotional intelligence has a positive and significant impact on employee performance; work family conflict has a positive and significant impact on employee performance through job satisfaction; and work family conflict has a positive and significant